2020
DOI: 10.5194/acp-20-9855-2020
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between urbanization and aerosols during a typical winter haze event in Beijing

Abstract: Abstract. Aerosols cause cooling at the surface by reducing shortwave radiation, while urbanization causes warming by altering the surface albedo and releasing anthropogenic heat. The combined effect of the two phenomena needs to be studied in depth. The effects of urbanization and aerosols were investigated during a typical winter haze event. The event, which occurred in Beijing from 15 to 22 December 2016, was studied via the Rapid-Refresh Multiscale Analysis and Prediction System – Short Term (RMAPS-ST) mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The consequences of urbanization (i.e., the transition from rural to urban surfaces) on atmospheric conditions are evident (Folberth et al, 2015), and they affect both the climate (Zhao et al, 2014; Published by Copernicus Publications on behalf of the European Geosciences Union. P. Huszar et al: The regional impact of urban emissions 2017; Huszar et al, 2014;Karlický et al, 2018Karlický et al, , 2020 and air pollution (Freney et al, 2014;Timothy and Lawrence, 2009;Butler and Lawrence, 2009;Im and Kanakidou, 2012;Huszar et al, 2016a), as well as the possible interactions between them (e.g., Huszar et al, 2018bHuszar et al, , 2020aHan et al, 2020;Fan et al, 2020) that often lead to complex counteracting effects (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of urbanization (i.e., the transition from rural to urban surfaces) on atmospheric conditions are evident (Folberth et al, 2015), and they affect both the climate (Zhao et al, 2014; Published by Copernicus Publications on behalf of the European Geosciences Union. P. Huszar et al: The regional impact of urban emissions 2017; Huszar et al, 2014;Karlický et al, 2018Karlický et al, , 2020 and air pollution (Freney et al, 2014;Timothy and Lawrence, 2009;Butler and Lawrence, 2009;Im and Kanakidou, 2012;Huszar et al, 2016a), as well as the possible interactions between them (e.g., Huszar et al, 2018bHuszar et al, , 2020aHan et al, 2020;Fan et al, 2020) that often lead to complex counteracting effects (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al. (2020) analyzed the mechanisms of the impacts of aerosols and urbanization using model, and found that aerosols reduced urban‐related warming during the daytime by 20% as fine particles concentrations increased and also enhanced urban‐related warming at dawn conversely. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Y. showed that aerosol radiation interaction (aerosol-cloud interaction) regulates and reduces the winter UHI intensity in Beijing, with the UHII at the time of daily maximum/minimum temperature exhibiting a decreasing/increasing tendency as PM 2.5 concentration increases. Yu et al (2020) analyzed the mechanisms of the impacts of aerosols and urbanization using model, and found that aerosols reduced urban-related warming during the daytime by 20% as fine particles concentrations increased and also enhanced urban-related warming at dawn conversely. Li et al (2018Li et al ( , 2020 examined potential interactions between urban pollution islands and UHI in Berlin, Germany, and found that urban pollution islands are negatively correlated with atmospheric UHI, but they cause higher surface UHI at night.…”
mentioning
confidence: 99%
“…Severe haze events caused by particulate matter have occurred regularly in China during recent decades, bringing health hazards and reducing atmospheric visibility [1][2][3][4]. These events have drawn worldwide attention, with many studies reporting frequent severe pollution in China's most developed regions [5,6]. Beside the influence of local emissions and further atmospheric chemical reactions [7], regional transport also plays a key role in pollution episodes [8,9].…”
Section: Introductionmentioning
confidence: 99%